On three new Euathlus tarantulas from Argentina and cladistic analysis of the genus - Ferretti, Nelson Edgardo (2015)
Three unknown species of Euathlus Ausserer 1875 (Araneae: Theraphosidae) are recognized and formally described. Euathlus diamante Ferretti sp. nov., E. sagei Ferretti sp. nov., and E. tenebrarum Ferretti sp. nov. are described from the Mendoza and Neuque´n provinces of western Argentina. The cladistic analysis showed Euathlus as monophyletic supported by the following synapomorphies: i) male tibial apophysis with fused branches bases; ii) presence of a ventral spine on retrolateral branch of male tibial apophysis; iii) sternum longer than wide. According to this cladistics analysis, a tree topology of (Homoeomma uruguayense (Mello-Leitao 1946) (Plesiopelma longisternale (Schiapelli & Gerschman 1942) (Grammostola anthracina (C.L. Koch 1842) (Phrixotrichus scrofa (Molina 1788) (E. tenebrarum sp. nov. (E. truculentus L. Koch 1875, E. sagei sp. nov. ((E. parvulus (Pocock 1903) (E. condorito Perafan & Pérez-Miles 2014, E. manicata (Simon 1892), E. atacama Perafan & Pérez-Miles 2014)) (E. antai Perafan & Pérez-Miles 2014, E. diamante sp. nov.)))))))) is reported.